Objetos de aprendizagem: seu potencial de reuso na prática da educação ambiental para a população negra - Dias, Juçara dos Santos Ferreira (2014)
This work is motivated by the concern expressed by educators with the use of technology in education in the context of environmental education, when the Brazilian reality is black majority in the classroom of public education. Your goal is to investigate the potential of Learning Object reuse for the study of the environment in a critical approach, paying attention to the occurrence of the practice of environmental racism. In this sense, we sought to understand the reasons which led to environmental education as a topic to be addressed in Brazilian education, reflecting on the environmental education in the postmodern scenario and its specificity in dealing with issues that affect the majority of black people. The following is the identification of learning objects available for the study of the environment, so that it is feasible to point out the learning object features in the reuse potential is satisfactory and meets the issues related to teaching and learning processes, including Join the black population. The research is characterized as applied, qualitative and exploratory. The applied technical procedure was the content analysis. How locus, the International Bank of Educational Objects was elected (BIOE) as Learning Object search field (OA) focused on the study of the environment. It was concluded that the critical study of perspective of the environment can be achieved with the use of OA with a greater degree of reuse, in which it seeks, through its content, favor the approach of specific issues, such as environmental racism.